Estimation of photovoltaic potential on residential rooftops using empirical Bayesian estimator - Villavicencio, J. [UNESP]; Melo, J. D. [UNESP]; Feltrin, A. Padilha [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Assessment of the photovoltaic generation potential on rooftops residential homes is performed by the calculation of the available areas for the installation of solar panels. However, socioeconomic factors could limit this installation for some people. Thus, this paper presents a methodology to estimate the photovoltaic potential using installation rates subject to the socioeconomic characteristics. The installation rates represent the preferences of the inhabitants to install this energy source and are calculated using global and local empirical Bayesian estimators. The result of the proposed methodology is a thematic map that allows the visualization of the spatial distribution of installation rates to identify regions with higher preference values, consequently, location of the greater photovoltaic electricity generation potential.
Keywords: electrical distribution systems; Empirical Bayesian estimators; photovoltaic systems